2017
DOI: 10.1212/wnl.0000000000004248
|View full text |Cite
|
Sign up to set email alerts
|

Motor speech signature of behavioral variant frontotemporal dementia

Abstract: Objective: To provide a comprehensive description of motor speech function in behavioral variant frontotemporal dementia (bvFTD).Methods: Forty-eight individuals (24 bvFTD and 24 age-and sex-matched healthy controls) provided speech samples. These varied in complexity and thus cognitive demand. Their language was assessed using the Progressive Aphasia Language Scale and verbal fluency tasks. Speech was analyzed perceptually to describe the nature of deficits and acoustically to quantify differences between pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 39 publications
3
46
0
8
Order By: Relevance
“…In addition, contrary to some prior research on bvFTD, we found no diagnostic group differences in standard deviation of fundamental frequency. This negative finding aligns with other research, however, and may represent differences in statistical technique, the speech elicitation task, and/or in the sample selection (e.g., bvFTD is a heterogeneous disorder, and may be prone to unrecognized differences in prosodic accommodation between subtypes).…”
Section: Discussionsupporting
confidence: 88%
“…In addition, contrary to some prior research on bvFTD, we found no diagnostic group differences in standard deviation of fundamental frequency. This negative finding aligns with other research, however, and may represent differences in statistical technique, the speech elicitation task, and/or in the sample selection (e.g., bvFTD is a heterogeneous disorder, and may be prone to unrecognized differences in prosodic accommodation between subtypes).…”
Section: Discussionsupporting
confidence: 88%
“…rated all audio recordings blinded to the presence of MS and disease severity. Twenty-six speech characteristics were analysed [25] ( Table 1). Briefly, a normal or unremarkable speech feature was scored as zero, whereas increasing deviation was scored using a four-point ordinal scale (e.g.…”
Section: Perceptual Analysismentioning
confidence: 99%
“…It is reasonable to assume that any condition that slows speech rate would affect cognitive scores derived from verbal output. Similarly, where individuals present with concomitant cognitive and motor deficits, the competing demands of each process can place stress on each domain, potentially leading to exacerbation of the perceived deficit in a formal testing setting (68,69). This is not unique to MSpeople with Myasthenia Gravis (a disease of the neuro-muscular junction) scored below controls in all NPT requiring a verbal response (and in one test that required rapid hand response) but normally in other NPT (70).…”
Section: Considerationsmentioning
confidence: 99%